2017
DOI: 10.1007/s00038-017-0949-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in healthy life expectancy between older migrants and non-migrants in three European countries over time

Abstract: Objectives We analysed differences in healthy life expectancy at age 50 (HLE50) between migrants and non-migrants in Belgium , the Netherlands, and England and Wales, and their trends over time between 2001 and 2011 in the latter two countries. Methods Population, mortality and health data were derived from registers, census or surveys. HLE50 and the share of remaining healthy life years were calculated for non-migrants, western and non-western migrants by sex. We applied decomposition techniques to answer whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 26 publications
5
43
0
Order By: Relevance
“…We defined migrants, our main independent variable, as those respondents who were not born in their current country of residence. As in previous migrant health research [ 6 , 20 23 ], we distinguished between migrants with a western or non-western origin. We defined western migrants as those born in Europe (except Turkey), North America, Oceania or Japan [ 6 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We defined migrants, our main independent variable, as those respondents who were not born in their current country of residence. As in previous migrant health research [ 6 , 20 23 ], we distinguished between migrants with a western or non-western origin. We defined western migrants as those born in Europe (except Turkey), North America, Oceania or Japan [ 6 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…These studies showed that, regardless of a generally lower socioeconomic status, migrants tend to live longer than non-migrants; this so-called ‘migrant mortality paradox’ has been observed across the life course, including at older ages [ 4 , 5 ]. However, previous research has also acknowledged that, compared to non-migrants, older migrants in Europe can expect to live a smaller number of years and a smaller share of their remaining life expectancy in good health [ 6 ]. Indeed, compared to older non-migrants, older migrants in Europe tend to have poorer self-rated health, more chronic conditions, worse functioning and higher rates of depression [ 4 , 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations